Regional Potential Analysis Based on Agricultural Commodities in Economic Development of Ternate City - Burhan Abdurahman; Said Assagaf; M. Janib Achmad (Agrikan: Jurnal Agribisnis Perikanan, 2020)
The development of the agricultural area in the city of Ternate is intended to create an equitable economic area throughout the city of Ternate. For this reason, research on the analysis of agricultural potential in the economic development of Ternate City is very important. This study aims, to determine the superior agricultural commodities in Ternate City, with LQ (location quotient) analysis. The results of LQ analysis can be seen that the commodity identified as the base commodity, namely palawijaya plant consisting of cassava, sweet potato and peanut corn, has the highest LQ value of 2.24 in West Ternate. Horticultural crops, namely mango, durian, breadfruit, salak, mangosteen and papaya, the highest LQ value was 0.93 in Moti sub-district. Whereas for horticultural crops, namely Chili, Long Beans, Cucumber, Onion, Kale, Tomato, Eggplant and Spinach, the highest LQ value was 1.4 8 in South Ternate.